Оптические свойства наночастиц серебра в полиметакрилатной матрице - Баженова, Ольга Александровна (Перспективы развития фундаментальных наук. Т. 2 : сборник научных трудов XIX Международной конференции студентов, аспирантов и молодых ученых, 26-29 апреля 2022 г.)
Currently, one of the actively developing areas of analytical chemistry is the creation of sensors based on nanomaterials. Polymethacrylate plates were chosen as a solid carrier for stabilization and formation of silver nanoparticles. Synthesis of silver nanoparticles in polymethacrylate was carried out by immobilization of silver ions from an aqueous solution of AgNO3. The information about the methods of obtaining silver nanoparticles and their optical properties was provided